171k views
0 votes
If f(x) = x2-x+3, what would the function look like once you substitute in a -3 to find

f(-3)?

Can someone answer really quick please .

User Technoh
by
4.7k points

2 Answers

3 votes

Answer:

havent learned that yet

Explanation:

User Giovanni Colitti
by
5.6k points
2 votes

Answer:


\huge \boxed{f( - 3) = 15}

Explanation:


f(x) = {x}^(2) - x + 3

To find f(-3), substitute the value of x that's - 3 into f(x). That is for every x in f (x) , replace it with - 3

We have


f( - 3) = ({ - 3})^(2) - ( - 3) + 3 \\ = 9 + 3 + 3 \\ = 9 + 6 \: \: \: \: \: \: \:

We have the final answer as


f( - 3) = 15

Hope this helps you

User Saurabh Mahajan
by
5.5k points